Students’ Oral Presentation Problems and Teacher`S Role in their Solutions - Kurbonova Oysha Beknazarovna (International Journal on Integrated Education, 2022)
The present article deals with the importance of oral presentation of learners and its challenges, as well as teacher’s role in their solutions.